Excavation protection of the Paromlin city library construction pit in Zagreb (Proceedings of Faculty of Civil Engineering, 2024)
The choice for the construction pit protection is extremely important in order to ensure the safety of workers, neighboring buildings and the environment during construction. The specific conditions of the construction site, geological conditions, the depth of the pit and the nearby infrastructure are crucial for the selection of the stabilization method of the construction pit. The paper provides an insight into several variant solutions for securing the construction pit of the Paromlin city library in Zagreb, for which a calculation was made in the PLAXIS 2D software package based on numerical analysis, i.e. the finite element method, taking into account the geotechnical characteristics of the soil determined by investigation work, the depth of the pit, environmental conditions, project requirements, legal and safety aspects, and economic feasibility. In order to choose the most suitable method of pit stabilization, a calculation was carried out for seven variant solutions on the relevant cross-section, all of which can be classified into three types of the construction pit protection: steel sheet piles, pilot rock design, and reinforced concrete diaphragm design.
Keywords: construction pit; numerical modeling; finite element method; numerical modeling, finite element method; steel sheet piles; pilot rock; diaphragm; PLAXIS 2D